Adaptation, validation and cut-off values of the Ages & Stages questionnaire 3th edition (ASQ-3) Spanish version in a Lima, Perú urban setting. - Gudiel-Hermoza, Adriel (2021)
Objective: A cultural-linguistic adaptation of the Age and Stages Questionnaire third edition (ASQ-3)-Spanish version was performed in order to determine its reliability, validity and cut-off points in an urban population and pediatric outpatient setting of Lima, Perú.  Material and Methods: Questionnaire forms were applied to parents of children between 1 to 66 months old of age, chosen through a convenience sampling method. Results: A total of  5,830 questionnaires were applied to parents of 3,507 children, 2 667 (45.7%) of whom had between 14 and 36 months of age. The general internal consistency and that of five specific areas, measured by means of the Ordinary alpha index oscillated between 0.70-0.94. Content validity by judges’ criteria, using the index by Lawshe method, the Aiken V coefficient, or both, was  valid for most of the questionnaires. The biserial item-test correlations were > 0.30 for most items (p <0.010). The construct validity according to the factorial analysis, determined that the five factors or areas of the ASQ-3 were adequate. Cut-off points were determined by age and area intervals of ​​the ASQ-3. Conclusions: The Spanish version of the ASQ-3 proved to be a reliable and valid tool to survey and screen the psychomotor development of children under 5 years of age in an urban outpatient area setting of ​​Lima, Perú.